2002
DOI: 10.1089/10849780252824073
|View full text |Cite
|
Sign up to set email alerts
|

Irradiated Cells from Autologous Tumor Cell Lines as Patient-Specific Vaccine Therapy in 125 Patients with Metastatic Cancer: Induction of Delayed-Type Hypersensitivity to Autologous Tumor is Associated with Improved Survival

Abstract: This patient-specific, cell culture-derived, autologous tumor cell vaccine induced anti-tumor immune reactivity that was associated with improved survival in patients with advanced cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 15 publications
1
20
0
Order By: Relevance
“…Equally important, the trial also showed the impracticality of using autologous tumor cells as vaccine components, a fact previously demonstrated by us 20 and others. [40][41][42] These findings support further clinical evaluation of vaccines comprised of TGF-b antisense-modified tumor cells in glioma and other tumors associated with systemic immunosuppression related to TGF-b2 secretion, but they also suggest that the use of allogeneic tumor cells may provide a practical alternative to autologous tumor cells.…”
Section: Discussionmentioning
confidence: 63%
“…Equally important, the trial also showed the impracticality of using autologous tumor cells as vaccine components, a fact previously demonstrated by us 20 and others. [40][41][42] These findings support further clinical evaluation of vaccines comprised of TGF-b antisense-modified tumor cells in glioma and other tumors associated with systemic immunosuppression related to TGF-b2 secretion, but they also suggest that the use of allogeneic tumor cells may provide a practical alternative to autologous tumor cells.…”
Section: Discussionmentioning
confidence: 63%
“…In October 2007 she enrolled in a randomized phase-II trial (NCT00436930) in which patients receive either the irradiated tumor cell or dendritic cell vaccine products that had previously been described. [1][2][3][4] She was randomized to the dendritic cell vaccine. She underwent a leukopheresis from which dendritic cells were generated, and these were combined with her irradiated tumor cells from her 2 cell lines.…”
Section: Vaccine-induced Cr In Melanoma 555mentioning
confidence: 99%
“…[1][2][3] In 74 patients with metastatic melanoma, who were treated with an irradiated tumor cell vaccine derived from an autologous tumor cell line, a median survival of 20.5 months was observed, and at a median follow-up of 6 years, the 5-year survival was 29%. 2 In a subsequent trial, in 54 patients with metastatic melanoma treated with a patient-specific vaccine consisting of autologous dendritic cells loaded with antigen from the patient's autologous tumor cell line, the median survival was >5 years with a 54% 5-year survival for all-cause mortality at a median follow-up of 4.5 years.…”
Section: Introductionmentioning
confidence: 99%
“…This is a highly personalized therapy and requires the generation of either short-term cultures or fully characterized cell lines derived from the tumor. This has been attempted in a number of tumors including melanoma [23,24] and sarcoma [25]. This has variable success rates and does pose the question: why should an autologous vaccine elicit an effective immune response by the patient, when the tumor, in situ, did not?…”
Section: Whole-cell Vaccinesmentioning
confidence: 99%